Rocky Mountain Geo-Conference 2016 : proceedings of the 2016 biennial Rocky Mountain Geo-Conference, November 4, 2016, Golden, Colorado - Strickland, Jere; Wiltshire, Richard L.; Goss, Christoph M. (The American Society of Civil Engineers, 2016)
"Contains 15 peer-reviewed papers on the complex geotechnical challenges in the Rocky Mountain region. Topics include: the evaluation, design, and rehabilitation of earthen dams; debris flows and landslide mitigation; compaction and low mobility grouting; seepage analysis on levees; drill parameters; load testing; and tunneling. GPP 10 focuses on geotechnical practice and experience in Colorado and the Rocky Mountain West; however, it will be of interest to practitioners working in any similar geologic setting."--ASCE website.
Sponsored by the Geo-Institute of the American Society of Civil Engineers, Geo-Institute Chapter of the Colorado Section of the American Society of Civil Engineers, Mile High Chapter of the Association of Environmental and Engineering Geologists and Colorado Association of Geotechnical Engineers.
Keywords: Geotechnical engineering -- Colorado -- Congresses.; Geotechnical engineering -- Rocky Mountains -- Congresses.; Landslide hazard analysis -- Colorado -- Congresses.; Landslide hazard analysis -- Rocky Mountains -- Congresses.; Earth dams -- Colorado -- Maintenance and repair -- Congresses.; Earth dams -- Rocky Mountains -- Maintenance and repair -- Congresses.; Soil stabilization -- Colorado -- Congresses.; Soil stabilization -- Rocky Mountains -- Congresses.; elektronické knihy; electronic books